HUBUNGAN KEBIASAAN KONSUMSI FAST FOOD DAN PENGETAHUAN GIZI TERHADAP OBESITAS PADA SISWA SMP NASIMA SEMARANG - Oktaviani, Marita Ayu; Tursilowati, Susi; Mintarsih, Sri Noor; Susiloretni, Kun Aristiati (Poltekkes Kemenkes Semarang, 2015)
National Riskesdas in 2013 reached 2.5%. Preliminary research found the prevalence of obesity in class VII and VIII students of Nasima Semarang Middle School at 22.3%.Objective: To determine the relationship between fast food consumption habits and nutritional knowledge with obesity in students of Nasima Semarang Middle School.Research Methods: This type of research is community nutrition with a case control method. The number of research samples was 50 students and 50 control students. The data collected were BB, TB, consumption habits of western fast food, fast food consumption habits, and nutritional knowledge using the interview method using a questionnaire. To find out the relationship between variables used Chi-Square test and Fisher Exact test with 95% confidence level.Research Results: The results of the study showed that the frequency of western fast food consumption bulan 29 times / month in obese samples was 54% while the normal sample was 20%. The frequency of fast food local consumptionâ‰¥71 times / month in obese samples was 56% while the normal sample was 14%. The level of knowledge of malnutrition in obese samples was 62% while the normal sample was 26%.Conclusion: There is a relationship between the consumption habits of western fast food with obesity (p = 0,000, OR = 4,694), there is a relationship between local fast food and obesity (p = 0,000, OR = 7.82), and there is a relationship between knowledge of nutrition and obesity (p = 0,000, OR = 4.64). It is recommended to carry out regular weight and height weighing and counseling activities related to obesity. In addition, further research is needed to find out other factors that affect obesity such as stress factors, economic factors, and physical activity.